Very long life fatigue failure mechanism of electron beam welded joint for titanium alloy at elevated temperature. (November 2021) - Liu, Fulin; Chen, Yao; He, Chao; Wang, Chong; Li, Lang; Liu, Yongjie; Wang, Qingyuan
Highlights: Very long life fatigue behavior of TC17 welded joints at 400℃ was investigated. Intergranular welded pores are responsible for fatigue failure. The unique facets at 400℃ were discovered for TC17 welded joints. The formation of facets is related to columnar grain and is driven by shear stress. Abstract: The very long life fatigue failure mechanism of welded joints for titanium alloy at 400℃ has been investigated. The results show that the welded joint has a nonhomogeneous microstructure. The welded defects are mainly welded pores, and maximum pore sizes are evaluated by statistical methods. The increase in temperature reduces the fatigue strength and changes the shape of S-N curves for the welded joints. Crack initiation is attributed to the existence of welded pores. Crystallographic facets are found around welded pores on the crack initiation zone, and their formation is sensitive to columnar grains and is driven by shear stress at 400℃.